Familial dicentric translocation t(13;18)(p13;p11.2) ascertained by recurrent miscarriages. Issue 1 (February 1979) - Daniel, A; Perel, I D; Clarke, A J; Saville, T
Abstract : A dicentric translocation is described involving chromosomes 13 and 18 in which the centromere of chromosome 13 was suppressed. The translocation was ascertained by repeated miscarriages and was found in three generations of phenotypically normal carriers.